The role of the legal division of the Medan City government in the preparation of academic manuscripts for draft regional regulations - Pasaribu, Fransisko; Sihotang, Januari (Priviet Social Sciences Journal, 2025)
This research illuminates the role and utilization of academic drafts (naskah akademik) in shaping regional laws (Perda) at the Medan City Government. This study seeks to ascertain the contribution of scholarly articles to enhancing the quality, legitimacy, and harmonization of regional law. Using a qualitative-descriptive approach and analysis of documents at the local level, such as local government reports, legal documents, and secondary data, this study finds that academic manuscripts serve as the scientific and legal basis for each step of the policy-making process. The results show that the Medan City Government, through cooperation with the DPRD and Kemenkumham, emphasizes manuscript hearings as a way to provide philosophical, sociological, and juridical justification for each bill. However, from the study, significant implementation bottlenecks have also been found, such as weak human resource capacity, weak institutional coordination, and insufficient public participation. This means that there is often duplication and delay in legal harmonization. For the successful implementation of regional legislation, governance needs to be promoted on the basis of preventive legal harmonization, capacity building, and participatory approaches. Therefore, academic papers should not just be perfunctory qualifications, but  tools of knowledge-based governance based on evidence, legality, and the people.